Anabolic-androgenic steroids and dietary supplements among resistance trained individuals in western cities of Saudi Arabia - Ameen Mosleh Almohammadi; Anas Mohammed Edriss; Turki Talal Enani (BMC, 2021)
Abstract Background Anabolic-androgenic steroids (AAS) contain testosterone-like androgens and are used as supplements to improve performance, therapeutic measures, appearance, and muscular development. Purpose This study aimed to estimate using anabolic-androgenic steroids (AAS) and good and bad practices about dietary supplements among resistance-trained individuals. It further seeked to determine the use of common drugs and supplements containing anabolic steroids among resistance-trained individuals (who work out at the sports centre) and assess users' knowledge about its side effects. Methods A cross-sectional survey was conducted at the sports centres of the western cities of Saudi Arabia. A self-administered questionnaire was used to collect data from 120 male resistance-trained individuals. Results The majority of the participants (80%) reported that they had not used any hormonal bodybuilding supplement last year, while 20% said they had used such hormonal supplements. Approximately half (52.5%) of participants reported that they always used dietary supplements. A total of 44.2% of participants possessed inadequate knowledge of these products. The main reason behind the use of hormones and supplements was to increase muscle mass. Conclusions A minority of resistance-trained individuals in the studied population frequently misused AAS. However, the results cannot be generalised to the whole of Saudi Arabia. AAS consumption can be reduced by enhancing the level of awareness and knowledge of potential adverse health outcomes.